2017
DOI: 10.1515/polyeng-2016-0409
|View full text |Cite
|
Sign up to set email alerts
|

Influence of mold temperature and process time on the degree of cure of epoxy-based materials for thermoset injection molding and prepreg compression molding

Abstract: Abstract A new hybrid process for fiber-reinforced plastics based on thermosets combining master-forming and forming in one tool is currently undergoing development. The advantage of this technique is the integrated forming and overmolding of a thermoset-based continuous fiber-reinforced sheet in one step. Although both components are epoxy based, the resin formulations slightly differ and thus require individual curing parameters. For successful combination into one process, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Hot compression molding is utilized for thermoplastic polymer composite production, where heat is needed to melt the polymer. However, for some thermoset composites, heat is applied to accelerate the curing process and enhance the mechanical properties [ 118 ]. However, one of the major difficulties in processing fast-cure thermoset resins is their strong exothermic reaction during curing.…”
Section: Thermosetting Polymer Composite Processingmentioning
confidence: 99%
“…Hot compression molding is utilized for thermoplastic polymer composite production, where heat is needed to melt the polymer. However, for some thermoset composites, heat is applied to accelerate the curing process and enhance the mechanical properties [ 118 ]. However, one of the major difficulties in processing fast-cure thermoset resins is their strong exothermic reaction during curing.…”
Section: Thermosetting Polymer Composite Processingmentioning
confidence: 99%
“…In the injection molding process, both thermosets and thermoplastics polymer are used, but the process included with thermoset is difficult to execute [40], [41]. The process parameter of thermosets such as curing time, curing temperature, injection pressure, and injection torque were investigated by Deringer et al [42] for epoxy-based natural fiber composite. An schematic setup of injection molding process is given in Fig.…”
Section: Injection Moldingmentioning
confidence: 99%
“…The difference in mechanical properties for 200 °C and 180 °C could result from the different crosslinking states. In [30] it is shown that different degrees of curing can result from processing epoxy resin at different mold temperatures, which have a direct influence on the mechanical properties. However, at 160 °C the complete wetting and impregnation of the rovings wasn't possible.…”
Section: Viscositymentioning
confidence: 99%
“…Considering Figure 7 (left), the short-glass-fibers are orientated parallel to the carbon-fibers, which resembles an orientation in flow direction. This corresponds to the state of the art of the injection molding of short-fiber-reinforced polymers [30,31]. Meier et al shows that for LCM processes, parts without reinforcement are filled first due to the fact that the liquid thermoset follows the path of lowest resistance [32].…”
mentioning
confidence: 99%